Serum levels of hormones regulating appetite in patients with cystic fibrosis − a single-center, cross-sectional study - Galiniak, Sabina; Podgórski, Rafał; Rachel, Marta; Mazur, Artur (Frontiers in Endocrinology, 2022)
Cystic fibrosis (CF), which is the most common inherited genetically determined disease caused by a mutation in the gene for the CF transmembrane conductance regulator protein. Pulmonary failure is the leading cause of death in this population, while the dysregulation of endocrine system creates significant disorders, including malnutrition, underweight, and CF-related diabetes. Therefore, the objective of our study was to determine the following hormones in the serum of patients with CF: ghrelin, putative peptide YY (PYY), Agouti-signaling protein (ASP), and alpha-melanocyte-stimulating hormone (α-MSH). To our knowledge, serum levels of PYY, ASP, and α-MSH have not yet been assessed in CF. For this purpose, we measured hormone levels using enzyme-linked immunosorbent assays in 38 patients from the local CF care center, as well as 16 sex- and age-matched healthy controls. Moreover, we estimated the correlations between the tested hormones and the parameters of the patients’ clinical status. In this study, we found sinificantly reduced serum levels of ghrelin and ASP in patients with CF (p<0.01). There was no difference in PYY and α-MSH levels between participants with CF and healthy subjects. Furthermore, there was no difference in hormone levels between females and males with CF. The type of gene mutation (homozygous or heterozygous for ΔF508) had no effect on hormone levels. Ghrelin was negatively correlated with age, body mass index, and C-reactive protein. PYY was negatively associated with the age of the patients. Hormone dysregulation in CF may contribute to decreased appetite, as well as many other disturbed processes. Therefore, ghrelin appears to play a key role in the regulation of energy management of CF. Future multicenter and multidisciplinary studies should focus on an unequivocal understanding of the role of these hormones in CF.